(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Trace elements are not essential in the same way as primary nutrients, as plants can survive and grow without them as long as they are provided with sufficient amounts of primary nutrients. Optimal growth and development may require the presence of trace elements in the appropriate amounts. Trace elements however possess their effects on the plants as well as animals. This study discusses the effects of trace elements on plants, animals and humans, with examples. Early research emphasis on the nutritional relevance of Si for plant development and growth, more recent research has switched its focus to silica’s effect on human health. Yet, the vast majority of Si, or dietary silica, originates from plants. The presence of silicon in the majority of cells as well as in fundamental species such as bacteria, viruses, and fungi provide support for the idea that Si is necessary in mammals. Root growth suppression is the principal consequence of Pb poisoning in plants, most likely because cell division is suppressed at the root tip. Roots of the Lemma minor plant showed evidence of Pb’s ability to impede cell division. Root dry mass and length were reduced in response to Pb poisoning in various plant species. On the other hand, too much zinc can damage the pancreas, interfere with protein metabolism, and cause arteriosclerosis. Respiratory issues may result from using zinc chloride for an extended period of time. While outbreak of zinc exposure at work may cause metal fever, a virus-like illness. Meanwhile, the amount of chromium that crops absorb can also be impacted by soil acidification. Plants often only absorb chromium (III). Following these examples, the chapter unfolds different aspects of benefits as well as harmfulness of trace elements.